(untitled) (Journal of Engineering, 2013)
During the last decade, there has been a concern about the relation between aluminum residuals in treated water and Alzheimer disease, and more interest has been considered on the development of natural coagulants. The present study aimed to investigate the efficiency of alum as a primary coagulant in conjunction with mallow, Arabic gum and okra as coagulant aids for the treatment of water samples containing synthetic turbidity of kaolin. Jar test experiments were carried out for initial raw water turbidities 100, 200 and 500 (NTU). The optimum doses of alum, mallow, Arabic gum and okra were 20, 2, 1 and 1 mg/L for100 NTU turbidity level, 35, 4, 2 and 3 mg/L , for 200NTU turbidity level and 50, 8, 10 and 8 mg/L for 500 NTU turbidity level, respectively. The optimum pH was 7 for alum, and 7.5 for mallow, Arabic gum and okra. The residual turbidity was 3.34 to 6.81 NTU by using alum as a primary coagulant with mallow, Arabic gum and okra, and pH values of the treated water by the natural coagulants were 6.1 to 7.01. The optimum dose of the natural coagulants in the present study has higher efficiency in removing high turbidity in comparison with low turbidity. Natural coagulant showed many advantages in coagulation/flocculation process. By using natural coagulants, considerable decreasing in Al2(SO4)3 consumption, and Increasing in the rate of sedimentation can be achieved.